Amikacin: Uses, Resistance, and Prospects for Inhibition - Ramirez, Maria S. (Molecules, 2017)
Aminoglycosides are a group of antibiotics used since the 1940s to primarily treat a broad spectrum of bacterial infections. The primary resistance mechanism against these antibiotics is enzymatic modification by aminoglycoside-modifying enzymes that are divided into acetyl-transferases, phosphotransferases, and nucleotidyltransferases. To overcome this problem, new semisynthetic aminoglycosides were developed in the 70s. The most widely used semisynthetic aminoglycoside is amikacin, which is refractory to most aminoglycoside modifying enzymes. Amikacin was synthesized by acylation with the l-(−)-γ-amino-α-hydroxybutyryl side chain at the C-1 amino group of the deoxystreptamine moiety of kanamycin A. The main amikacin resistance mechanism found in the clinics is acetylation by the aminoglycoside 6′-N-acetyltransferase type Ib [AAC(6′)-Ib], an enzyme coded for by a gene found in integrons, transposons, plasmids, and chromosomes of Gram-negative bacteria. Numerous efforts are focused on finding strategies to neutralize the action of AAC(6′)-Ib and extend the useful life of amikacin. Small molecules as well as complexes ionophore-Zn(+2) or Cu(+2) were found to inhibit the acetylation reaction and induced phenotypic conversion to susceptibility in bacteria harboring the aac(6′)-Ib gene. A new semisynthetic aminoglycoside, plazomicin, is in advance stage of development and will contribute to renewed interest in this kind of antibiotics.